EL FUNDAMENTO METAFÍSICO DE LAS TEORÍAS ADMINISTRATIvAS - Hidalgo Sáchez, Augusto (2013)
The management science emerged one century ago thanks to pioneer models of normative inspiration. Later, new theories of sociological and psychological nature were added to that body of knowledge. After de Second World War, the uprising of the applied mathematics in business improved the management of the organizations and their environment. Lately, a new stream of systemic nature is generating not only a new kind of business model but of business thinking. In sum, it is possible to state that there are four sources of administrative metaphysics: normative, sociological, mathematical and systemic. We suggest that the research procedures in universities should change in order to incorporate to the traditional quantitative approach, new qualitative ones born from the fountain of the three other metaphysics.